Cost Analysis of Insecticide Spraying For Malaria Control In A Terai District Of Eastern Nepal (Health Renaissance, 2016)
Background: Malaria is one of the public health problems in Nepal. It is estimated that 25% of population of Nepal are infected by malaria at any time. Malaria control program was first initiated in 1954 with support of USAID through the Insect Born Disease Control Program. This program was changed into Malaria Eradication Program in 1958. The program was reverted to control program in 1978.Objective: The objective of this study was to estimate the cost of insecticide spraying from the provider’s perspective in a Terai district of eastern Nepal.Methods: Morang District of eastern Terai was purposively selected. A pre-tested interview was used to collect data from program managers and government officers in the Malaria Control Program. The main categories of variables were manpower, insecticide, pump and others.Results: The cost for indoor residual spraying per person protected was calculated as Rs.24.70 (US$0.31). This cost was for one cycle and there were two cycles in a year. So the cost per year was Rs.49.40 (US$0.62). The cost per household was calculated as Rs. 129.56 (US$1.65) per cycle and Rs.259.12 and US$3.30 per year for residual spraying.Conclusion: In this cost analysis of indoor residual spraying, the cost per household per year was found Rs. 259.12 and US$3.30. The cost calculated per person protected per year was Rs. 49.40 and US$0.62. This analysis would be more complete if a comparative study of both costs and effectiveness of various vector control measures are undertaken in Nepal.Health Renaissance 2014;12(3): 175-179